AI-Powered Chatbots: Revolutionizing Auto Insurance Policy Selection and Management - SaratBabu Vamkeswaram, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the transformative impact of AI-powered chatbots on the auto insurance industry, focusing on policy selection and management processes. It shows how intelligent virtual assistants are revolutionizing customer service and operational efficiency across the insurance value chain. The article analyzes the technical architecture of modern insurance chatbots, including their Natural Language Processing capabilities and data integration frameworks. It investigates core functionalities for new policy selection, automated renewal management, and advanced analytics systems. The article also addresses critical aspects of security and compliance in insurance technology implementations. Through a comprehensive analysis of business impact and return on investment, the article demonstrates how digital transformation initiatives are enhancing both operational efficiency and customer experience. Additionally, the study outlines future development roadmaps, focusing on enhanced AI capabilities and platform evolution in the insurance sector. The article highlights how sophisticated technology integration and continuous improvement in chatbot systems are establishing new standards for customer service efficiency and satisfaction in the insurance industry.
Keywords: Insurance Chatbots; Artificial Intelligence; Policy Management; Digital Transformation; Customer Experience